Successful treatment of donor‐derived hepatitis C infection in a lung transplant recipient. Issue 2 (22nd February 2017) - Theodoropoulos, Nicole; Whitson, Bryan A.; Martin, Stanley I.; Pouch, Stephanie; Pope‐Harman, Amy
Abstract: Data are limited regarding the use of direct‐acting antivirals for treatment of hepatitis C infection post lung transplant, especially in a donor‐derived infection. We present a case of a lung transplant recipient with donor‐derived hepatitis C that was successfully treated with a 12‐week regimen of simeprevir and sofosbuvir. This case reiterates the importance of screening recipients of increased‐risk donor organs for disease transmission and the value of early therapy.